Early Decompression and Short Transport Time After Traumatic Spinal Cord Injury are Associated with Higher American Spinal Injury Association Impairment Scale Conversion. Issue 1 (1st January 2022) - Sterner, Robert C.; Brooks, Nathaniel P.
Abstract : To date, the optimal timing of surgical decompression of traumatic spinal cord injury patients remains controversial. This retrospective cohort study suggests an association of early surgical decompression within 12 hours and short transport times (<6 hours) with significant improvements in neurological outcomes. Abstract : Study Deign: Retrospective cohort study. Objectives: This retrospective cohort study aims to determine the association of early decompressive surgery and the impact of transport time on the neurological outcomes of traumatic spinal cord injury (tSCI) patients. Summary of Background Data: tSCI is a catastrophic event that may result in permanent disability or loss of function. To date, there remains significant controversy over the optimal time for surgical decompression in tSCI patients. The aim of this study is to evaluate the neurological outcomes of tSCI patients undergoing early versus late surgical decompression and the impact of transport time on neurological outcomes. Methods: Data from 84 patients with tSCI requiring surgical decompression was collected. Regression analysis was used to establish time to decompression classification cutoffs. Patients were classified into the following subgroups: 0 to 12 or >12 hours as a factor of the total or admitting hospital time to decompression. The change in American Spinal Injury Association Impairment (AIS) Grade from admission to discharge was determined. Additionally, the effect of transport time on conversion of AIS grade was assessed as patients were grouped into transport times of <6 or >6 hours. Result: Among the time to decompression subgroups there were no significant differences ( P > 0.05) in confounding factors such as age, injury severity, and AIS grade. Patients who received decompression within 0 to 12 hours were associated with significantly ( P < 0.0001) higher average improvements in ASIA grade (0.76). Patient transport times <6 hours were associated with significantly ( P = 0.004) higher conversion of AIS grade to less impaired states. Conclusion: The present study suggests an association of decompression within 12 hours and short transport times (<6 hours) with significant improvements in neurological outcomes. Level of Evidence: 4